Sharpening the Tandem Walking Test for Screening Peripheral Neuropathy - Cohen, Helen S. (2013)
OBJECTIVE: Few tests of functional motor behavior are useful for rapidly screening people for lower extremity peripheral neuropathy. The goal of this study was to improve the widely used Tandem Walking test (TW). METHODS: We tested adult normals and ambulatory peripheral neuropathy patients (PN) with eyes open and eyes closed, while they performed TW on industrial carpeting, in sock-covered feet. Each subject wore a torso-mounted inertial motion unit to measure kinematic data. PN subjects’ data were also compared to historical data on patients with vestibular impairments (VI). RESULTS: The normal and PN groups differed significantly on TW on the number of steps completed. PN and VI data also differed significantly on both visual conditions. Kinematic data showed that PN patients were more unstable than normals. For the number of steps taken during the eyes open condition receiver operating characteristic (ROC) values were only 0.81. For the number of steps taken during the eyes closed condition, however, ROC=0.88. Although not optimal, this ROC value is better. Sensitivity and specificity at a cut-off of 2 steps were 0.81 and 0.92, respectively, and at a cut-off of 3 steps was 0.86 and 0.75, respectively. ROC values for kinematic data were all < 0.8 and, when combined with the ROC value for the number of steps, the total ROC value did not improve appreciably. CONCLUSIONS: Although not ideal for screening patients who may have peripheral neuropathy, counting the number of steps during TW is a quick and useful clinical test. TW is most sensitive to peripheral neuropathy patients when they are tested with eyes closed.